Online Impulse Buying In M-Commerce Context : Website Quality, Trust, and Flow Condition - Kristanto, Damar; Suharto, Bambang; Aly, M. Nilzam (International Journal of Psychosocial Rehabilitation, 2020)
The rise in impulsive buying behavior when shopping online using smartphones providing a challenge for businesses to design their online store website into mobile versions. This raises the question of how impulsive buying can occur in online store context moreover through smartphone devices. In that case, this study aims to determine the effect of a mobile version online store website quality on customer flow condition, online trust, and impulsive buying. This research using a non-probability sampling method and the technique used is purposive sampling. Data were collected from 294 respondents in Indonesia. The analysis technique used in this research is Partial Least Square (PLS). As a results show that the online store website quality has a positive influence on online trust, and flow condition. Online trust also has a positive effect on flow condition and impulsive buying. And at last, the flow condition also has a positive effect on online impulsive buying. Marketers and web-developers can take a cue from this research and enhance the effectivity of online store websites especially when they want to compress it for the smaller screen like a smartphone.